The functional addition of hydrochloric acid to dry feed improves mineral nutrition, growth, and reduces body deformities in juvenile stomachless tench - R. Kamiński; J. Sikorska; L. Polak-Juszczak; J. Wolnicki (Animal)
The rapid growth of aquaculture production is accompanied by environmental challenges, an important factor of which is the release of phosphorus into aquatic ecosystems. Phosphorus released from aquaculture contributes to the eutrophication of freshwater ecosystems. Improving the efficiency of assimilation of phosphorus contained in feed can help reduce phosphorus-induced pollution. Supplementing dry fish diets with inorganic acids appears to be a simple and cost-effective method of increasing the availability of key dietary minerals, including phosphorus, to fish. This is especially effective for species lacking a functional stomach which are unable to digest food in an acidic environment. This group includes cypriniform fish, many of which play a significant role in global aquaculture. One such species, tench (Tinca tinca), is an important species for aquaculture in several European countries. In this study, different doses (0.75, 1.5, and 3.0%) of hydrochloric acid were used as functional additives to commercial dry feed for tench juveniles. The 57-day experiment was carried out in recirculating aquaculture systems. The dietary additive of HCl affected the fishes’ whole-body phosphorus content and phosphorus use efficiency, as well as the content of calcium, magnesium, strontium, chromium, incidence of body deformities, growth, condition factor, and feed conversion ratio. The body contents of potassium, sodium, iron, zinc, copper, manganese, cadmium, and lead were not affected by adding HCl. The highest share of individuals with body deformities (10%) was recorded in fish fed the basal diet. In contrast, among fish fed a diet with HCl, body deformities (2%) were found only in the group with the lowest acid dose. Moreover, the 1.5% additive of HCl to the diet gave the best results regarding fish growth rates and feed conversion. Therefore, this dietary additive of HCl was proven to effectively promote the growth of juvenile tench, protect fish from body deformities, and reduce pollution caused by phosphorus waste generated during intensive fish farming.